Spectral theory for bounded banded matrices with positive bidiagonal factorization and mixed multiple orthogonal polynomials - Branquinho, Amílcar; Foulquié-Moreno, Ana; Mañas, Manuel (Advances in mathematics (New York. 1965), 2023)
Spectral and factorization properties of oscillatory matrices lead to a spectral Favard theorem for bounded banded matrices, that admit a positive bidiagonal factorization, in terms of sequences of mixed multiple orthogonal polynomials with respect to a set positive Lebesgue–Stieltjes measures. A mixed multiple Gauss quadrature formula with corresponding degrees of precision is given.